Comparative analyses of pathogenesis-related protein-10 (PR10) in plants - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2017)
In the present study, we have comparatively analyzed PR10 genes and proteins from 28 plant species in order to understand the relationship (conservation or divergence) between different PR1Os in various plant species. In analyzed species, PR10 proteins were found to be small (157-166 as long and 14.3-18.2 kDa weight) and acidic (4.69-6.17) in nature. Besides, PR10 sequences had highly conserved GxGGxG motif (P-loop motif) structure at various positions. These positional variations in glycine (Gly) residues may become the result of substitution, deletions and insertions occurred during the course of PR10 evolution. In general, primary sequences of PR1Os in various plant species may have a well conserved structure. Digital expression data of tomato and maize showed that expression of PR10 genes may significantly increase in plant parts (root, lateral root and root tips) where it is more open to the mechanical perturbation and pathogenic attack, supporting the involvement of PR10 in plant defense. In phylogenetic tree, a clear monocot/polycot and dicot separation were observed. This separation could have been arising from the well conserved structure of PR10 genes of monocots and polycots than dicots. All modeled species contained the same number of beta-strands (seven) but alpha-helices varied between 2 and 4 depending on species. The results of this study will provide a theoretical reference regarding the primary, secondary and tertiary structure of PR1Os in various plant species and will support the future studies that aiming to characterize the pathogenesis-related (PR) proteins.
Keywords: In silica; pathogenesis-related protein 10; 3D structure; phylogenetic; polycot; divergence; LIGAND-BINDING SITES; BET V 1; DISEASE RESISTANCE; STRESS TOLERANCE; GENES; EXPRESSION; RICE; ACID; INDUCTION; FAMILY